Sistema de gestão da qualidade para empresas construtoras de pequeno porte - Felipe Cancado Bicalho (2009)
Although there are uncertainties that characterize the Brazilian building construction sector the market share of small companies in this segment has grown and in most cases they focus their attention on the construction of buildings for the middle class. These companies - that are most frequently held by only one owner or director - are not well structured when it comes to management, whether considering the administrative point of view or the management of the enterprises. These companies are not familiar with standards for quality management systems, and for several reasons, it is often difficult to implement the NBR ISO 9001 : 2008 or the SiAC Construtoras on the range of the PBQP-H. It should be specially emphasized that the amount of procedures and the bureaucracy inherent in the NBR ISO 9001 : 2008/SiAC are frequently incompatible with the structure of these companies. Therefore, this work suggests a model of quality management that takes care of the particularities of the small construction companies, focusing on basic aspects of the management of the enterprises. The following elements constitute this model: the management of the documentation associated with the enterprises and the communication, which are based on the Proposição Alternativa Para Qualificações de Empresas de Projeto (MELHADO 2006), an adaptation to the Plano de Qualidade das Obras, including control of processes (referred on SiAC Construtoras), the planning system and the work inspection based on the Lean Thinking, the critical analysis of design and the acquisition of cost indices as well as of productivity. In parallel, an exploration study has been carried out regarding to small constructioncompanies in order to characterize this universe of study and understand the context where these companies work. The study points to the convenience of one thinking about a specific quality management system for these companies. The model was implemented in a small family construction company that had been recently formed during the execution of a residential building of eight units. The qualitative analysis of the results indicates a better control of the productive process, more confidence on the planning, waste and rework reduction, besides a better work on the structure of the company, having in mind standard small companies as a compatible model. On the other hand, the implementation of the model seems to be the first step for the introduction of a continuous improvement in the company, making possible the creation of a management structure that may further allow the development of the quality management system.